The science of gymnastics - Monem, J.; Sands, W. A.; Salmela, J. H.; Holvoet, P.; Gateva, M. (Routledge, 2011)
Comprehensive and accessible introduction to the fundamental physiological, biomechanical and scientific principles underpinning this most demanding of sporting disciplines. Drawing on cutting edge scientific research, and with contributions from leading international sport scientists, the book represents an important link between theory and performance. With case studies, data and useful review questions included in every chapter, the book examines every key aspect of gymnastic training and performance, including: physiological assessment; diet and nutrition; energetics; strength and conditioning; growth and development; anthropometric and biomechanical models; kinetics and kinematics; stress, anxiety and coping; motivation and goal setting; and, the psychology of learning and performance. There is a concluding section that breaks down a series of core gymnastic techniques and movements into their fundamental scientific components, helping the student to better understand how sport science relates to sporting performance. Examines the key aspect of gymnastic training and performance, including - physiological assessment; diet and nutrition; energetic; strength and conditioning; growth and development; anthropometric and biomechanical models; kinetics and kinematics; stress, anxiety and coping; and, motivation and goal setting.